THE CONTRIBUTION OF EMOTIONAL INTELLIGENCE AND INTERPERSONAL COMMUNICATION ON TEACHER PERFORMANCE THROUGH JOB SATISFACTION - Sari, Adny Novita; Sulaiman; Suriansyah, Ahmad (Indonesian Researcher Society for Science Technology and Education (IDREST) Publisher, 2019)
This study aims to analyze the contribution of emotional intelligence and interpersonal communication to teacher performance through teacher job satisfaction. This research uses quantitative descriptive methods. A sample of 194 people from 377 teachers spread across 13 high schools in Banjarmasin. Data were extracted using a questionnaire that has been valid and reliable and analyzed using Path Analysis. The results showed that: (1) There was a direct contribution between emotional intelligence, interpersonal communication, job satisfaction, and teacher performance (2) There was an indirect contribution between emotional intelligence, interpersonal communication through job satisfaction as an intermediary variable on the performance of teachers at the SMAN Banjarmasin City. This study concludes that significant results are obtained for all variables studied.